PHYSICAL ACTIVITY IN ADOLESCENTS AS THE BASIS OF A HEALTHY LIFESTYLE - Czarnecki, D.; Skalski, D. W.; Rybak, O.; Graczyk, M.; Dovgan, O.; Starikov, V. (Rehabilitation and Recreation, 2022)
The most important factors that have a significant impact on health and life expectancy are physical activity. Physical activity is one of the main components of a healthy lifestyle. There is a common belief that physical activity is one of the most important categories that determine the proper functioning of the human body. Leading an active lifestyle has many benefits. The benefits of physical activity are obvious. Systematic physical activity is a very strong biological stimulator and is one of the main determinants of human physical and mental health. Its optimal level stimulates development, secures motor needs, strengthens the heart efficiency, improves the flexibility of muscles and joints, and strengthens muscles and bones. Therefore, specific forms of physical activity include not only sports exercises, but also physical effort related to active movement, e.g. to work, school, work, doing all kinds of housework and physical activity in free time). Physical activity is, of course, associated with a very varied energy expenditure, depending on the intensity of exercise / physical effort, its duration, environmental temperature or body weight of the person performing the physical effort. It has been proven that active people, compared to inactive people, feel better and experience less mental or physical ailments, such as low mood or headaches. Physical activity is commonly perceived as associated with intensive practice of various sports. Meanwhile, you don't need to be a seasoned runner or an excellent swimmer to achieve the level of physical activity that will positively affect our health. Bearing in mind the above conditions, an attempt was made to diagnose this phenomenon, focusing mainly on school students aged 15-17. They wanted to find out what level of knowledge in terms of physical activity and its impact on health is represented by students, and what lifestyle they lead themselves. The main goal of this publication is the desire to indicate the importance of this extremely important issue and the need for a direction of change in the field of health education of the young generation. Promoting physical activity is still a topical and important task.